2011
DOI: 10.1063/1.3582135
|View full text |Cite
|
Sign up to set email alerts
|

Edge energy transport barrier and turbulence in the I-mode regime on Alcator C-Mod

Abstract: We report extended studies of the I-mode regime [D. G. Whyte et al Nucl. . This regime, usually accessed with unfavorable ion B×∇B drift, features an edge thermal transport barrier without a strong particle transport barrier. Steady I-modes have now been obtained with favorable B×∇B drift, by using specific plasma shapes, as well as with unfavorable drift over a wider range of shapes and plasma parameters. With favorable drift, power thresholds are close to the standard scaling for L-H transitions, while with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
135
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(153 citation statements)
references
References 31 publications
18
135
0
Order By: Relevance
“…
The excitation of a novel kind of heavy particle [1,2] mode at the edge of the plasma column is considered as the signature of the I-confinement Regime [3][4][5][6][7]. The outward transport of impurities produced by this mode is in fact consistent with the observed expulsion of them from the main body of the plasma column (a high degree of plasma purity is a necessary feature for fusion burning plasmas capable of approaching ignition).
…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…
The excitation of a novel kind of heavy particle [1,2] mode at the edge of the plasma column is considered as the signature of the I-confinement Regime [3][4][5][6][7]. The outward transport of impurities produced by this mode is in fact consistent with the observed expulsion of them from the main body of the plasma column (a high degree of plasma purity is a necessary feature for fusion burning plasmas capable of approaching ignition).
…”
mentioning
confidence: 59%
“…Another feature of the mode that predicted by the theory is that the I-Regime exhibits a knee of the ion temperature at the edge of the plasma column but not one of the particle density as the mode excitation factor is the relative main ion temperature gradient exceeding the local relative density gradient. The net plasma current density appearing in the saturation stage of the relevant instability, where the induced particle and energy fluxes are drastically reduced, is associated with the significant amplitudes of the poloidal magnetic field fluctuations [6,7] observed to accompany the density fluctuations. The theoretical implications of the significant electron temperature fluctuations [10] observed are discussed.…”
mentioning
confidence: 99%
“…The I-mode plasmas are of particular interest because of their attractive confinement features [10,11] and because the edge heat and particle transport are more de-coupled than in H-mode, allowing for a large temperature pedestal and high energy-confinement (H 98 <1.2) without a density pedestal and without ELMs regulating the edge pressure. Thus the edge profile gradient-scale-lengths for T e are similar in I-mode and H-mode, while the edge gradient-scale-lengths for n e are different, with L ne I-mode, ped ~ 10xL ne H-mode,ped [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a natural lack of ELMs, 3 I-mode does not suffer from H-mode-like impurity accumulation, even in a metal-walled machine such as Alcator C-Mod. [4][5][6] I-mode is generally run with the ion B Â rB drift away from the active X-point (unfavorable rB drift), which enables a more robust access to the I-mode confinement regime. 5 I-mode appears in a power window between L-mode and H-mode, and it has been found that this power window opens up significantly at a higher magnetic field.…”
Section: Introductionmentioning
confidence: 99%